Hypoxia regulates Notch-3 mRNA and receptor activation in prostate cancer cells. Issue 5 (May 2016) - Meunier, Armelle; Flores, Angela Nilda; McDermott, Niamh; Rivera-Figueroa, Karla; Perry, Antoinette; Lynch, Thomas; Redalen, Kathrine Røe; Marignol, Laure
Abstract: The Notch-3 receptor is a recognized key regulator of vascular responses and is increasingly associated with tumorigenesis. Hypoxia-inducible factors activate specific signaling pathways such as Notch in a number of cellular models. This study aimed to evaluate the regulation of Notch-3 by hypoxia in prostate cancer cells. Notch-3 gene and protein expression was established in a panel of aerobic and hypoxic prostate cell lines in vitro, the CWR22 xenograft model and RNA extracted from low grade (Gleason score < = 6); high grade (Gleason score > = 7); non-hypoxic (low HIF, low VEGF); hypoxic (high HIF, high VEGF) patient FFPE specimens. NOTCH-3 was upregulated in PC3 (3-fold), 22Rv1 (4.1-fold) and DU145 (3.8-fold) but downregulated in LnCaP (12-fold) compared to the normal cell lines. NOTCH-3 expression was modified following hypoxic exposure in these cells. NOTCH-3 was upregulated (2.2-fold) in higher grade and hypoxic tumors, when compared to benign and aerobic pools. In the CWR22 xenograft model, Notch-3 expression was restored in castrate resistant tumors. Nuclear translocation of the Notch-3 intracellular domain was no longer detected following exposure of cells to hypoxia but not associated with a change in expression of HES-1. Our data further identifies Notch-3 as a potentially key hypoxic-responsive member of the Notch pathway in prostate tumorigenesis.